The clinical relevance of lipid transfer protein. Issue 1 (1st December 2017) - Asero, R.; Piantanida, M.; Pinter, E.; Pravettoni, V.
Summary: Despite a huge number of studies, many aspects of the lipid transfer protein (LTP) syndrome, the most frequent primary food allergy in Mediterranean countries, remain unclear. Its peculiar geographical distribution, along with the extreme variability of its clinical expression, makes this type of food allergy something unique in the panorama of IgE‐mediated food‐induced allergic reactions. This review article tried to summarize the current knowledge about the most important aspects of LTP sensitization and allergy, along with the importance of positive and negative co‐factors in the clinical expression of the syndrome as well as the issues regarding the cross‐reactivity between LTPs present in botanically related and unrelated foods. Further, the possible absence of the protein from some plant foods is discussed.